Grandmaster of demonic cultivation = Mo dao zu shi. 5 - Moxiangtongxiu (Seven Seas Entertainment, 2023)
Wei Wuxian and Lan Wangji are headed for a showdown at Guanyin Temple, where their path converges with Jin Guangyao and Nie Mingjue's reassembled fierce corpse. With decades-long schemes finally unveiled, and terrible secrets unearthed, the events of this rain-battered night will decide not just the future of the entire cultivation world...but also that of a love story two lifetimes in the making. Also included in this final volume are eight short stories about what happens when an epic tale ends but life goes on. From magical incense burners to tense banquets, lotus-pod-hunting to Night Hunts with the juniors--these stories span dawn to dusk and so much more!